2005
DOI: 10.1042/bj20041888
|View full text |Cite
|
Sign up to set email alerts
|

Activation of protein synthesis in cardiomyocytes by the hypertrophic agent phenylephrine requires the activation of ERK and involves phosphorylation of tuberous sclerosis complex 2 (TSC2)

Abstract: The hypertrophic Gq-protein-coupled receptor agonist PE (phenylephrine) activates protein synthesis. We showed previously that activation of protein synthesis by PE requires MEK [MAPK (mitogen-activated protein kinase)/ERK (extracellular-signal-regulated kinase) kinase] and mTOR (mammalian target of rapamycin). However, it remained unclear whether ERK activation was required and which downstream components were involved in activating mTOR and protein synthesis. Using an adenovirus encoding the MKP3 (MAPK phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
79
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(90 citation statements)
references
References 59 publications
8
79
1
1
Order By: Relevance
“…44,46 Recent evidence has highlighted that mTOR can also be activated by Raf/MEK/ERK. 59,60 This may well be another relevant cross talk between the Ras/Raf/MEK/ERK and the PI3K/ PTEN/Akt/mTOR pathways and might offer a further rationale for treatments combining drugs which inhibit both signaling networks. A diagram illustrating potential targets in these signal transduction pathways to target is presented in Figure 5.…”
Section: Targeting Different Cascades For Leukemia Therapy Ja Mccubrementioning
confidence: 99%
“…44,46 Recent evidence has highlighted that mTOR can also be activated by Raf/MEK/ERK. 59,60 This may well be another relevant cross talk between the Ras/Raf/MEK/ERK and the PI3K/ PTEN/Akt/mTOR pathways and might offer a further rationale for treatments combining drugs which inhibit both signaling networks. A diagram illustrating potential targets in these signal transduction pathways to target is presented in Figure 5.…”
Section: Targeting Different Cascades For Leukemia Therapy Ja Mccubrementioning
confidence: 99%
“…Given that these MEK inhibitors also activate AMPK, which clearly complicates the interpretation of these experiments, we used an alternative approach to inhibit the Erk signalling cascade and hence Rsk. MIN6 cells were infected with recombinant adenovirus encoding Mitogen-activated protein kinase phosphatase 3 (AdMPK3), a dualspecific phosphatase that dephosphorylates the activation loop of ERK1/2 with very high specificity 22 , and its effect on GLP1 stimulated rpS6 phosphorylation was assessed (figure 3b). The phorbol ester TPA, which potently activates Erk and Rsk, was used a positive control (figure 3b).…”
Section: Inhibition Of Phosphoinositide 3-kinase Reveals That Glp1 Anmentioning
confidence: 99%
“…RSK1 and RSK2 play a pivotal role in regulating a variety of biological functions including inhibition of apoptosis (14,15), activation of the mTOR pathway (16), and cell proliferation (17,18). RSK1 and RSK2 have also been shown to play an important role in the proliferation of breast and prostate tumor cells (17,18) and in augmenting cardiac hypertrophy (19). Previous studies from our laboratory have shown that the inactive form of RSK1 associates with PKARIā£, and upon its activation, RSK1 binds PKAc (20).…”
mentioning
confidence: 99%